The Influence of Training And Work Motivation on the Performance of B&F (Food and Beverage) Employees - Mayna Divadana, Kadek; H. Sihombing, Irene Hanna; Suastini, Ni Made (Ridwan Institute, 2024)
This study investigated the impact of training and work motivation on employee performance among 78 B&F (Food and Beverage) employees. The data collected was both quantitative and qualitative. A saturated sampling technique was employed, and the results were analyzed using multiple linear regression with SPSS version 23. The findings indicate that both the Training Variable (X1) and Work Motivation Variable (X2) have significant partial effects on Employee Performance, with t-count values exceeding the t-table value and significance values less than 0.05. Furthermore, the simultaneous effect of both variables on employee performance is also significant, with a t-count value greater than the t-table and a significance value less than 0.05. In conclusion, the study demonstrates that training and work motivation have a significant impact on employee performance among B&F employees.